ICT Strategic Planning in Malaysia Public Research Institute - Ishak, Iskandar Shah; Alias, Rose Alinda; Adam, U.; Suradi, Z. (IJEEEE, 2013)
ICT Strategic Planning (ICTSP) is important to an ICT manager because their wisdom in managing ICTSP implementation is being use as one of their performance indicators. Although there are many benefits for implementing ICTSP, ICT managers are still facing problems in coping with the development of ICTSP in their organization. Research Institute has unique characteristics that need to be look deeper to maximize the impact of their ICTSP implementation. This paper presents the comparison of research institutes characteristics against business organizations and institutes of higher learning. A survey questionnaire was sent to the Heads of IT in IPA. The results of the status study of ICTSP development and implementation in Malaysian Public Research Institute and Government Agencies (IPA) provide a better understanding of their requirements. The finding of the study showed that one of IPAs ICTSP aim is to promote innovation in their organization since they are a dynamic and innovative organization. The research also revealed that even though IPA had experienced in ICTSP development and implementation, they were still facing several problems in developing and implementing ICTSP using existing methodologies. The problem is related to the level of easiness and completeness of methodology used and the comprehensiveness of blueprint produce to gain the requested budget from the sponsor. In addition, the research also suggested that there is a need to customize the existing ICTSP methodology to fulfill research institutes unique characteristics and to maximize ICTSP impact to promote innovation in the organization.